Safety, pharmacokinetic and pharmacodynamic properties of single ascending dose and continuous infusion of remimazolam besylate in healthy Chinese volunteers - Sheng, Xiao-yan; Liang, Yan; Yang, Xue-yuan; Li, Li-e; Ye, Xia; Zhao, Xia; Cui, Yi-min (European journal of clinical pharmacology, 2020)
Purpose The aim of the present study was to evaluate the safety, pharmacokinetic (PK) and pharmacodynamic (PD) properties of remimazolam besylate following single ascending dose (SAD) and continuous infusion in healthy Chinese volunteers. Methods This was a randomized phase I study conducted in two parts. Part I was a double-blind, placebo- and midazolam-controlled, SAD study among healthy Chinese participants with a remimazolam dose of 0.025–0.4 mg/kg. Part II was an open-label, midazolam-controlled, continuous infusion study. Bispectral index (BIS) monitoring and Modified Observers Assessment of Alertness and Sedation (MOAA/S) score assessment were used to assess the PD properties. Results The half-life range of remimazolam was from 34.1 ± 8.1 to 59.8 ± 20.5 min in the SAD study. The sedation function was initially observed at the dose of 0.05 mg/kg remimazolam. Doses of ≥ 0.075 mg/kg exerted a peak sedation effect within 1–2 min after injection, resulting in a deeper and more rapid sedation. In the 2 h continuous infusion, remimazolam showed a deeper sedation and more rapid recovery than midazolam. For general anesthesia, an induction dosage of 0.2 mg/kg/min and a maintenance dosage of 1 mg/kg/h can achieve a satisfactory efficacy effect. Conclusions Remimazolam was safe and well tolerated in healthy Chinese participants. Based on the phase I clinical study, we suggest that remimazolam besylate demonstrates greater sedation and quicker recovery from sedation than midazolam.